LEGAL STUDY ON THE ACTION OF PKPU ADMINISTRATORS THAT CONDUCTED ILLEGAL INCREASE OF CREDITORS’ RECEIVABLES - Margareth Rae Sita (Syiah Kuala Law Journal, 2022)
This study aims to analyze the implementation of the duties and authorities of the Administrator in compiling the number of PKPU Creditors' receivables and the legal liability of the Administrator who illegally enlarges the number of PKPU Creditors' receivables using a normative juridical approach. This study concludes with several results. Firstly, the task and authority of the Administrator in compiling the number of Creditors' receivables based on Law Number 37 of 2004 is to receive all claims from Creditors and then match these claims with notes and reports held by the Debtor. In practice, some Administrators do not match claims in compiling the number of receivables. Secondly, the Administrator who illegally enlarges the number of PKPU Creditors' receivables can be held legally responsible based on Law Number 37 of 2004. If it has harmed the Debtor's assets, the Administrator can be sued through civil law based on Articles 1365 and 1366 of the Indonesian Civil Code.